Checklist of the familes Chaoboridae, Dixidae, Thaumaleidae, Psychodidae and Ptychopteridae (Diptera) of Finland - Salmela, Jukka (Pensoft Publishers, 2014)
Abstract. A checklist of the families Chaoboridae, Dixidae, Thaumaleidae, Psychodidae and Ptychopteridae (Diptera) recorded from Finland is given. Four species, Dixella dyari Garret, 1924 (Dixidae), Threticus tridactilis (Kincaid, 1899), Panimerus albifacies (Tonnoir, 1919) and Panimerus przhiboroi Wagner, 2005 (Psychodidae) are reported for the first time from Finland.